The Impact of Reviews on Consumer Purchase Decision in Educational Institutes of Lahore, Pakistan - Zarwish Bint E Ishaq; Arsalan Khalid; Abdul Ahad; Sameera Amjad (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
The research is on “Impact of reviews on consumer purchase decision”. The purpose of research was to study the impact of reviews on consumer purchase decision. The primary data was gathered by floating questionnaires. SPSS software was applied to analyze data for frequencies regression parameters. The findings suggested that user’s reviews have significant impact on consumers purchase decision. Consistent positive reviews from a trustworthy source have a positive impact on the purchase decision of the consumers. Consumers having a prior experience related to a product also lead to a significant positive relationship with the purchase decision. It is a quantitative research. Which is a systematic investigation by gathering quantifiable data and performing statistical techniques. Primary data was collected through questionnaires. Primary research was conducted in order to collect the data. Data type is also primary because research is instrument based. The sample size for my research is 300 responses. The main aim of this test was to find the relationship of purchase decisions with prior product expertise, informational influence, perceived review consistency, perceived review quality and value expression influence. Prior product expertise, informational influence and perceived review consistency had a significant impact on purchase decision. However perceived review quality and value expression influence had insignificant impact on purchase decision. Prior product expertise have a positive impact on purchase decision